Regulation of the AbrA1/A2 two-component system in Streptomyces coelicolor and the potential of its deletion strain as a heterologous host for antibiotic production. - Sergio Rico; Ana Yepes; Héctor Rodríguez; Jorge Santamaría; Sergio Antoraz; Eva M Krause; Margarita Díaz; Ramón I Santamaría (PLoS ONE, 2014)
The Two-Component System (TCS) AbrA1/A2 from Streptomyces coelicolor M145 is a negative regulator of antibiotic production and morphological differentiation. In this work we show that it is able to auto-regulate its expression, exerting a positive induction of its own operon promoter, and that its activation is dependent on the presence of iron. The overexpression of the abrA2 response regulator (RR) gene in the mutant ΔabrA1/A2 results in a toxic phenotype. The reason is an excess of phosphorylated AbrA2, as shown by phosphoablative and phosphomimetic AbrA2 mutants. Therefore, non-cognate histidine kinases (HKs) or small phospho-donors may be responsible for AbrA2 phosphorylation in vivo. The results suggest that in the parent strain S. coelicolor M145 the correct amount of phosphorylated AbrA2 is adjusted through the phosphorylation-dephosphorylation activity rate of the HK AbrA1. Furthermore, the ABC transporter system, which is part of the four-gene operon comprising AbrA1/A2, is necessary to de-repress antibiotic production in the TCS null mutant. Finally, in order to test the possible biotechnological applications of the ΔabrA1/A2 strain, we demonstrate that the production of the antitumoral antibiotic oviedomycin is duplicated in this strain as compared with the production obtained in the wild type, showing that this strain is a good host for heterologous antibiotic production. Thus, this genetically modified strain could be interesting for the biotechnology industry.